After the flood: a multidisciplinary investigation of human remains found in a floodplain and first record of raft spiders colonizing a corpse / Edda E. Guareschi and Paola A. Magni - Guareschi, Edda E.; Magni, Paola A. (Faculty of Medicine, 2021)
In the analysis of any forensic case, the estimation of time, cause and manner of death is affected by post-mortem changes. These are inextricably linked to both intrinsic characteristics of the body and a variety of external factors, mainly environmental, such as the presence and types of scavengers. While there are several research and case-studies on terrestrial environments, there is scant knowledge regarding aquatic environments, either stable or cyclical/seasonal. At present, no case studies have considered human remains discovered in the mud, following a flooding event. This case study describes a body discovered in a floodplain area in northern Italy. After a flood event, the water progressively drained out, leaving the body in the mud. Besides the unique conditions of the remains, of particular interest was the colonization by larvae of Calliphora vomitoria (L.) (Diptera: Calliphoridae) and raft spiders, Dolomedes fimbriatus (Clerck) (Araneae: Pisauridae), for the first-time recorded colonizing a corpse. The multidisciplinary approach to such an investigation is described.